Code Switching Used by Boy William in Breakout Program on Net Tv - Dwinesa Anggraeni; Hernalia Citra Dewi (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2020)
This research is carried out to find out (1) the types of code-switching used by Boy William in the “Breakout” program on Net TV, (2) the most dominant type of code-switching used by Boy William in “Breakout’’ program on Net TV? The researchers use the descriptive qualitative method by collecting the data from three episodes of Breakout TV program, the data was taken by focusing on Boy William utterances. It’s found 40 data that is classified into three types of code-switching, there are inter-sentential code-switching, intra-sentential switching, and tag switching. The research result shows that there are 4 inter-sentential code-switching used in Boy’ utterances, 35 intra-sentential, and 1 of tag switching. In brief, from three videos that the researchers observed there is 10% utterances of inter-sentential, 87,5 % using intra-sentential, and 2,5% tag switching used by Boy William in Breakout music program on Net TV. Then, intra-sentential code-switching is the most often used by the speaker. Keywords: sociolinguistics, code-switching, English learning